Financial risk management with taking account of information - Kuznietsova, N. V. (Інститут проблем реєстрації інформації НАН України, 2018)
The existing risk management methods, such as risk aversion, localization, diversification and risk compensation are investigated and the whole process of risk analysis based on the system methodology through the main stages: detection, analysis and minimization of risk is illustrated. The criterion for ta-king into account information risks through possible losses in the implementation of information threat is proposed. The main criteria for analyzing information risks through the assessment of the quality of data, the decisions taken and the adequacy of the modeling are given, and the own quadratic criterion is proposed to take into account the compensatory costs for combating the risks of both information and financial nature. Also, the system for financial risk management, which takes into account both informational and financial risks and forms a managerial decision is shown. The process of work of the risk management system is adaptive, that is, on the basis of the proposed criteria for assessing the quality of the decisions made, it is possible to accept, reject or re-develop a management solution based on the set of input data and modeling results. The proposed methodology for analyzing and evaluating information risks within financial risks has been implemented in a unified information technology on the SAS platform.